Can qualitative and quantitative methods serve complementary purposes for policy research?: evidence from Accra - Maxwell, Daniel G. (International Food Policy Research Institute, 1998)
Qualitative and quantitative methods in social science research have long been separate spheres with little overlap. However, recent innovations have highlighted the complementarity of qualitative and quantitative approaches. The Accra Food and Nutrition Security Study was designed to incorporate the participation of a variety of constituencies in the research, and to rely on a variety of approaches — both qualitative and quantitative — to data collection and analysis. This paper reviews the way in which qualitative and quantitative methods were used in the Accra study. The argument of the paper is that the complementary use of qualitative and quantitative approaches provides a greater range of insights and perspectives and permits triangulation or the confirmation of findings by different methods, which improves the overall validity of results, and makes the study of greater use to the constituencies to which it was intended to be addressed. But the search for truly complementary methods presents substantial challenges as well. These include extra costs, both in financial and human terms, ethical dilemmas regarding follow-up, and the need for teamwork and respect for different methodological and epistemological positions.